ОБ УВЕЛИЧЕНИИ ИНТЕРНАЦИОНАЛЬНЫХ СПОРТИВНЫХ ТЕРМИНОВ В КАРАКАЛПАКСКОМ ЯЗЫКЕ - Кощанов, К.М.; Калжанова, У.А. (SCIENCE and SOCIETY, 2024)
This article about the usage and borrowing a huge number of international sport terms in Karakalpak.